Dimensions of Social Diversity in Europe - Szewior, Krzysztof (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2019)
The aim of the publication is to learn the dimensions of social differentiation by applying socio- economic indicators, as well as to indicate the importance of economic and social conditions as the leading factors in building the social order of national states and the European Union. The main research question concerned the issue whether and under what conditions it is possible to achieve improvement in the level of social cohesion? The experience and knowledge allow to assume that the most important in achieving social and economic cohesion are: the level of economic development and socio-political consensus regarding the distribution and circulation of social goods, rather than the model of national social policy. The adopted assumption was verified, confirmed the dominant role of the social contract, the scope of social solidarism and the developed GDP. These elements determine social development and determine the competitive advantage of national economies. In view of the weakness of institutions and EU-wide solutions, they consolidate the multidimensional disproportions between European societies. The analysis is based on research methods of politics and social policy. Statistical data was provided by national and EU institutions.

Celem publikacji jest poznanie wymiarów społecznego zróżnicowania poprzez zastosowanie wskaźników społeczno-gospodarczych, a także wskazanie znaczenia uwarunkowań gospodarczych i społecznych jako wiodących czynników w budowaniu ładu społecznego państw narodowych oraz Unii Europejskiej. Zasadnicze pytanie badawcze dotyczyło kwestii czy i w jakich warunkach możliwe jest uzyskanie poprawy w poziomie spójności społecznej? Zebrane doświadczenie i wiedza pozwalają założyć, że istotniejsze w osiąganiu spójności społeczno-gospodarczej są: poziom rozwoju gospodarczego i konsensus społeczno-polityczny względem rozdziału i obiegu dóbr, niż model narodowej polityki społecznej. Przyjęte założenie zostało zweryfikowane, potwierdziło dominującą rolę umowy społecznej, zakresu solidaryzmu społecznego oraz wypracowanego PKB. Elementy te wyznaczają stan rozwoju społecznego oraz determinują przewagę konkurencyjną gospodarek narodowych. Wobec słabości instytucji i rozwiązań ogólnounijnych utrwalają wielowymiarowe dysproporcje między społeczeństwami europejskimi. Analiza bazuje na metodach badawczych nauki o polityce oraz polityki społecznej. Dane statystyczne dostarczyły instytucje krajowe i unijne.
Wymiary zróżnicowania społecznego Europy
Keywords: social diversity; inequality; inconsistency; EU social model; społeczne zróżnicowanie; nierówność; niespójność; model społeczny UE